Karakteristik Sistem Pembagian Waris Keluarga Dayak Muslim - Lestari, Indah; Syaikhu, H; Patrajaya, Rafik (Legal Standing : Jurnal Ilmu Hukum, 2025)
Inheritance practices between Muslim Dayak families can be handed over to the majority without regard to differences in religion and gender. This indirectly shows that there are values that are maintained by Muslim Dayak families in the distribution of inheritance so that this happens. This research is a type of empirical research with a legal sociology type and approach socio-legal with qualitative data analysis methods. The results of the research show that the implementation of inheritance distribution in Muslim Dayak families applies three main points, namely Budaya Damai, Tradisi Hakakat and implement the principles Belom Bahadat namely maintaining the value of the inheritance system used so as to create a characteristic, namely applying equality, so that Dayak Muslim inheritance can be in harmony with Islamic law.